1999
DOI: 10.1080/01904169909365675
|View full text |Cite
|
Sign up to set email alerts
|

Neotyphodium coenophialum‐endophyte infection affects the ability of tall fescue to use sparingly available phosphorus

Abstract: Neotyphodium coenophialum, (Morgan-Jones & Gams) Glenn, Bacon & Hanlin, infected tall fescue (Festuca arundinacea Schreb.) plants perform better than non-infected isolines on phosphorus (P)-deficient soils. Our objective was to characterize growth and P uptake dynamics of tall fescue in response to endophyte infection and P source at low P availability in soil. Two tall fescue genotypes (DN2 and DN4) infected with their naturally occurring N. coenophialum strains (E+), and in noninfected (E-) forms were grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 41 publications
4
82
0
Order By: Relevance
“…Additionally, it was shown that P use efficiency was greater in plants accessing P from the RP and TCP treatments compared to plants receiving adequate soluble P directly to their roots in the AAP treatments. Malinowski & Belesky (1999) also found that phosphorus use efficiency was 16% greater in endophyte-infected tall fescue plants than in non-infected plants. This suggests that P use efficiency is greater when P is supplied by the fungus.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, it was shown that P use efficiency was greater in plants accessing P from the RP and TCP treatments compared to plants receiving adequate soluble P directly to their roots in the AAP treatments. Malinowski & Belesky (1999) also found that phosphorus use efficiency was 16% greater in endophyte-infected tall fescue plants than in non-infected plants. This suggests that P use efficiency is greater when P is supplied by the fungus.…”
Section: Discussionmentioning
confidence: 91%
“…To a lesser extent, shoot and root biomass was greater in RP-treated plants than those receiving no P (0P). Malinowski & Belesky (1999) also found that root dry matter was greater in endophyte-infected tall fescue pastures fertilized with rock phosphate than in pastures fertilized with commercial fertilizer providing plant available P. Microscopic analysis revealed that roots in all treatments were internally colonized by A. ustus. Due to the variability in the nature and composition of internal DS fungal structures many of these structures are not microscopically visible making it impossible to accurately quantify their presence (Barrow & Aaltonen, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…Endophyte benefits to their host plants include enhanced drought tolerance (Arechavaleta et al, 1989;Malinowski et al, 1997), resistance to nematodes (Kimmons et al, 1990;West et al, 1988), and growth enhancements (Malinowski and Belesky, 1999). E. festucae was also found to enhance resistance to dollar spot disease caused by Sclerotinia homeocarpa (J. F. White, personal communication).…”
Section: Biological Plant Protectionmentioning
confidence: 96%
“…Fungal symbionts of the related genera Epichloë (which have a sexual state) and Neotyphodium (strictly asexual) are symbionts of many cool-season grasses (subfamily Pooideae) (Clay and Leuchtmann, 1989;, to which they provide a variety of fitness enhancements such as increased resistance to herbivory, parasitism, and drought, as well as growth enhancements (reviewed in Clay, 1990;Schardl and Clay, 1997) and improved nutrient acquisition (Malinowski and Belesky, 1999). Interest in these fungal "endophytes" at the turn of the 20th century was sparked by observations of toxicoses to animals grazing certain grasses.…”
Section: Taxonomy and Historymentioning
confidence: 99%
“…When more than 20 mL of fermented liquid was added, root biomass was reduced. This might be because high doses of fermented liquid adsorbed much Cd 2+ and reduced Cd 2+ -induced stress in rice root, so the rice foot fully absorb the nutrient elements in the soil, such as phosphorus [35] and nitrogen [36], and delivered them to the above-ground parts of the rice, making them grow rapidly. The synthesis of a large amount of organic matters increases the fresh weight of rice seedlings and finally improved rice growth.…”
Section: Influence Of Cn35 Strain On Rice Growth and Its Detoxificatimentioning
confidence: 99%